Самостійна робота студентів при вивченні дисципліни "Агроекологія" - Тодорова, Людмила Володимирівна; Тодорова, Людмила Владимировна; Todorova, Liudmyla (ТДАТУ, 2018)
UK: У статті аналізуються перспективні види і методи самостійної роботи студентів спеціальності "Агрономія" під час опанування матеріалу з дисципліни "Агроекологія". EN: The perspective types and methods of the self-work of students of the specialty "Agronomy" while mastering the material of "Agroecology" discipline were analyzed in the article.
Self-work of students in the study of "Agroecology" discipline
Keywords: формування професійних знань та вмінь; реферат; доповідь; дискусія; види; методи; formation of professional knowledge and skills; abstract; report; discussion